Effect of urogastrone on gastric secretion and serum gastrin concentration in patients with duodenal ulceration. Issue 11 (November 1982) - Koffman, C G; Elder, J B; Ganguli, P C; Gregory, H; Geary, C G
Abstract : A one-hour infusion of 0.25 micrograms/kg urogastrone administered to seven patients with duodenal ulceration resulted in significant reduction of basal acid secretion (p less than 0.05) but was without significant effect on basal pepsin and intrinsic factor secretion or on serum gastrin concentration. In another group of five patients with duodenal ulceration a one-hour infusion of urogastrone was given on five successive days. On day 1 and 5 urogastrone was administered after establishing a plateau response to intravenous pentagastrin 1.2 micrograms/kg/h. A mean reduction of 65% in acid output during the urogastrtone infusion was seen on day 1 and this was maintained during the next hour. On day 5 the pentagastrin-stimulated acid output was less than on day 1 and a further significant decrease was noted after urogastrone. Pepsin and intrinsic factor output were also significantly inhibited. There was no change in fasting serum gastrin or urogastrone concentration.